Ensino/Aprendizagem da rotação na 5ª série: um estudo comparativo em relação ao material utilizado - Mega, Élio (2001)
Starting from the premise that isometries should be included in the geometry curriculum, this research proposes that we should begin with rotations at 5th grade, by means of strategies of using easily obtainable manipulatives. This investigation compares the achievements of two groups of subjects along a sequence of activities that took place in the classroom, mediated only by the researcher; one of the groups was allowed to use only traditional drawing tools and the other one was instructed to employ alternative material and tools like sticks, tracing papers, buttons and the transpel , a device specially designed for this study. The activities were planned to fit in the framework of the theory of Piaget and Garcia concerning the psychogenesis of the geometrical thinking and the ideas of Meira related to the transparency of artifacts used in the teaching of Mathematics. The analysis of results in the activities and in the post-test has shown that there is a strong influence of the applied material in the students performance, dependent on the nature of the activity. The research concludes that both sets of manipulatives can contribute in different ways to enlarging students experience and understanding of the conceptual field of rotation